Integrating Low-Altitude Remote Sensing and Variable-Rate Sprayer Systems for Enhanced Cassava Crop Management - Pongpith Tuenpusa; Grianggai Samseemoung; Peeyush Soni; Thirapong Kuankhamnuan; Waraphan Sarasureeporn; Warinthon Poonsri; Apirat Pinthong (AgriEngineering)
Integrating remote-controlled (RC) helicopters and drones equipped with variable-rate sprayer systems represents a significant advancement in agricultural practices, particularly for the precise management of crop diseases. This study utilizes low-altitude remote sensing platforms to monitor crop growth and disease infestation, proposing advanced technology for managing and monitoring disease outbreaks in cassava fields. The performance of these systems was evaluated using statistical analysis and Geographic Information System (GIS) applications for mapping, with a particular emphasis on the relationship between vegetation indices (NDVI and GNDVI) and the growth stages of cassava. The results indicated that NDVI values obtained from both the RC helicopter and drone systems decreased with increasing altitude. The RC helicopter system exhibited NDVI values ranging from 0.709 to 0.352, while the drone system showed values from 0.726 to 0.361. Based on the relationship between NDVI and GNDVI of cassava plants at different growth stages, the study recommends a variable-rate spray system that utilizes standard instruments to measure chlorophyll levels. Furthermore, the study found that the RC helicopter system effectively measured chlorophyll levels, while the drone system demonstrated superior overall quality. Both systems showed strong correlations between NDVI/GNDVI values and cassava health, which has significant implications for disease management. The image processing algorithms and calibration methods used were deemed acceptable, with drones equipped with variable-rate sprayer systems outperforming RC helicopters in overall quality. These findings support the adoption of advanced remote sensing and spraying technologies in precision agriculture, particularly to enhance the management of cassava crops.